Static and dynamic performance of fibre reinforced composite panels - Ng, Denise Rui Qi (Nanyang Technological University, 2021)
Fibre composite is now widely used in various industry such as the aviation industry and commercial mechanical engineering field. The static and dynamic performance of the fibre composite is very critical to ensure reliability and safety. The objectives of this project were, to fabricate composite panels and specimens, conduct various tests on the specimens and further analyse to understand the fibre composite so that guidelines for quality optimisation can be provided. Through this project, specimens were successfully fabricated and tested in accordance with ASTM standards. The test procedures were discussed as it is a key parameter in ensuring the consistency and reliability of the test results. Results obtained from the tensile test and 3-point bending test show how the stacking sequence and fibre orientation can affect the mechanical properties. The results were compared and analysed to provide the guidelines for quality optimisation.